Main results of the second AIRP international radon-in-field intercomparison for passive measurement devices. (September 2019) - Berlier, F.; Cardellini, F.; Chiaberto, E.; Garlati, L.; Giuffrida, D.; Ragani, M. Faure; Leonardi, F.; Magnoni, M.; Minchillo, G.; Prandstatter, A.; Serena, E.; Trevisi, R.; et al.
Highlights: Considering reproducibility SSNTDs exhibit better performances than electrets. The effect of long time sampling (fading) is well managed by the laboratories. For high and low radon levels, passive devices did not show any fading effect. For mixed radon/thoron atmosphere: overestimation of radon exposure. Larger variability of results for mixed radon/thoron atmosphere.